Do Budgeting Practices Affect Saving Behaviour among Small Scale Entrepreneurs in Kenya? Evidence from Kisumu Central Constituency - Sarah, Komen Chepchirchir; Mule, Robert Kisavi (European Scientific Journal, ESJ, 2022)
World Bank Development Indicators’ most recent data reveals that the nation’s Gross Domestic Savings as a proportion of gross domestic product(GDP) was 11.09 percent in 2017, 11.64 percent in 2018, 11.25 percent in 2019 and 12.83 percent in 2020. This shows that the country’s domestic savings is increasing but relatively low. As a result of this the country presents a significant development challenge. Individuals need to learn the basic knowledge of financial areas so that people may make knowledgeable financial decisions about how to earn, spend, save, manage, and invest their money. The purpose of this study was to answer if budgeting practices has an effect on saving behavior among small scale entrepreneurs in Kenya. The study’s particular objectives were to; establish the influence of monitoring spending, financial planning and tracking spending pattern on saving behavior among small entrepreneurs. The study was guided by Life Cycle Theory and Financial Literacy Theory. Correlational research design was employed in the study. The target population comprised of 914 registered small entrepreneurs in Kisumu town central constituency who have been in business for at least 2 years. The study adopted Yamane sampling technique and obtained 278 respondents. Open-ended and closed-ended structured questionnaires were employed to gather primary data. To test reliability of the questionnaire, the study piloted 28 respondents who were excluded in the final study. The study then used Cronbach’s Alpha to test reliability. The results showed that budgeting practices (α=0.828) and budgeting practices (α=0.870) all had a strong alpha value of above 0.7 which indicates that the instrument is reliable. The study findings revealed that; monitoring spending was significant (β= .376; p=.000˂ 0.05) that is an increase of 1 unit in monitoring spending causes an increase of .376 units in saving behavior, financial planning was significant (β= .333, p=.000˂0.05) that is an increase of 1 unit in financial planning causes an increase of .333 units in saving behavior and tracking spending pattern was also significant (β= .179, p= .000˂0.05) that is an increase of 1 unit in monitoring spending terms causes an increase of .179 units in saving behavior. There was a strong positive and significant association between budgeting and saving behavior thus rejecting the null hypothesis. The study concludes that budgeting practices enhances saving behaviour of small entrepreneurs in Kenya and recommends that small scale entrepreneurs should practice all aspects of budgeting which includes monitoring spending, financial planning and tracking spending pattern should be among small scale entrepreneurs in Kenya. This will enable them to compare what they have spent with regard to what they had planned thereby helping them improve their saving behavior.